2018
DOI: 10.3390/en11030512
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Production, Combustion and Modeling of Furan-Based Fuels

Abstract: Abstract:There is growing interest in the use of furans, a class of alternative fuels derived from biomass, as transportation fuels. This paper reviews recent progress in the characterization of its combustion properties. It reviews their production processes, theoretical kinetic explorations and fundamental combustion properties. The theoretical efforts are focused on the mechanistic pathways for furan decomposition and oxidation, as well as the development of detailed chemical kinetic models. The experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 221 publications
(493 reference statements)
0
26
0
Order By: Relevance
“…Including recent progress in the characterization of its combustion properties, production processes, theoretical kinetic explorations and fundamental combustion properties. The theoretical efforts are focused on the mechanistic pathways for furan decomposition and oxidation, as well as the development of detailed chemical kinetic models 2018 [39] Furthermore, it is well-known that, the field of furan chemistry, both theoretically and in the applied segment is very huge, and no single work can exhaust its many applications that range, from the chemical, to electrical and electronics, pharmacy, biomedical, medicine, the textile, paints and coatings, plastics industry, to name but a few [2,[49][50][51]. Interestingly, according to the density functional theory (DFT) calculations, it has been shown that the heterocyclic furan ring is particularly prone to ring opening, preferably via the C-O bond [52], which can be harnessed for generating tailored and tuneable products, thereby, broadening the application portfolio of furanic systems whether in bio-refineries and/or application materials as has been exemplified in the work of Fan et al [53], when they demonstrated a self-crosslinking elastomeric thermoset via furan ring-opening mechanism.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Including recent progress in the characterization of its combustion properties, production processes, theoretical kinetic explorations and fundamental combustion properties. The theoretical efforts are focused on the mechanistic pathways for furan decomposition and oxidation, as well as the development of detailed chemical kinetic models 2018 [39] Furthermore, it is well-known that, the field of furan chemistry, both theoretically and in the applied segment is very huge, and no single work can exhaust its many applications that range, from the chemical, to electrical and electronics, pharmacy, biomedical, medicine, the textile, paints and coatings, plastics industry, to name but a few [2,[49][50][51]. Interestingly, according to the density functional theory (DFT) calculations, it has been shown that the heterocyclic furan ring is particularly prone to ring opening, preferably via the C-O bond [52], which can be harnessed for generating tailored and tuneable products, thereby, broadening the application portfolio of furanic systems whether in bio-refineries and/or application materials as has been exemplified in the work of Fan et al [53], when they demonstrated a self-crosslinking elastomeric thermoset via furan ring-opening mechanism.…”
Section: Historical Overviewmentioning
confidence: 99%
“…The joint optimization of fuel and propulsion systems can exploit the potential of efficient, ultra-low-emission combustion, using renewably made fuels or fuel additives. Chemistry knowledge is needed to tailor their combustion properties and understand the influence of their molecular structure on their reaction mechanisms [13] , [14] , [15] , [16] , [17] , [18] for current and advanced combustion conditions, as well as to determine efficient pathways to make such fuels sustainably and in large scale [17 , 18] .…”
Section: Setting the Stage: Combustion And Chemistry In Contextmentioning
confidence: 99%
“…The relationship between their molecular structure, reaction mechanism, and combustion behavior is an intense area of research, particularly for the development of predictive combustion models. Proposed fuel classes include, among others, cellulosic biofuels such as the furanic family [17 , 18] and synthetic fuels such as oxymethylene ethers (OMEs, CH 3 O(CH 2 O) n CH 3 ). The latter, attractive diesel replacement fuels, offer large pollutant reduction potential owing to their molecular structure featuring only C 1 units [21 , 22] .…”
Section: Setting the Stage: Combustion And Chemistry In Contextmentioning
confidence: 99%
“…42 Furan is a member of a class of bioprivileged molecules, which can be converted into other substances with high added value. 43,44 Furanic compounds can be chemically manipulated or used directly for many purposes. [45][46][47] For example, 5-hydroxymethylfurfural (HMF) is one of the most promising platforms for chemicals formed from hexoses.…”
Section: Introductionmentioning
confidence: 99%